Detector control systems and monitoring of the High Granularity Calorimeter for the upgrade of CMS - Toms, M.; Klute, M.; Taysi, C.; Yaz, K.; Kolcu, O. B.; Simsek, E.; Iren, E.; Parmar, N.; Cokic, L.; Tsirou, A. (IOP Publishing Ltd, 2026)
The CMS experiment at the LHC is building a new High-Granularity Calorimeter (HGCAL), based on silicon sensors and scintillator tiles read out by SiPMs, as part of the CMS detector Phase-2 upgrade. Silicon modules and SiPM-on-tile boards are integrated into cassettes prior to their insertion into the endcap structure. After assembly, the cassettes must be tested under cold conditions using cosmic muons. Cold operation of the cassettes inside specially designed cold boxes requires fully functional Detector Control Systems (DCS) and Subdetector Environmental Protection (SEP) systems. The objective is to provide operators with a convenient and reliable way to control and monitor a large number of hardware components, both inside and outside the cold box, while ensuring the safety of personnel and detector equipment. The experience gained from the development and practical operation of such systems at the Cassette Assembly Facility (CAF) at CERN will inform the design of control and protection systems for the final HGCAL detector at CMS. This paper presents the design of the control and protection systems for the HGCAL CAF at CERN, along with progress on their development, testing, and operation.
Keywords: Calorimeters; Detector control systems (detector and experiment monitoring and slow-control systems, architecture, hardware, algorithms, databases); Instruments & Instrumentation